Implementation of the Tpack-Based Project Based Learning (Pjbl) Learning Model to Increase Students' Learning Motivation in Class XI History Subjects SMAN 1 Gunungsari - Taufik Hidayat; Rosada (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
The objectives of this study are as follows: 1) To assess the learning motivation of students before the implementation of the "Project Based Learning" model in Class XI at SMAN 1 Gunungsari. 2) To evaluate the increase in students' learning motivation in history classes among Class XI students at SMAN 1 Gunungsari. The method employed was a class action research method with an experimental design. The population of this study consisted of Class XI students at SMAN 1 Gunungsari. Sampling was conducted using a cluster sampling technique with a non-equivalent control group design. Based on the research results obtained from the experimental class, it was found that the application of the Project-Based Learning model was able to enhance the learning motivation of Class XI students at SMAN 1 Gunungsari. This was evident from the increase in the percentage of average scores based on teacher observation results in cycle 1, where 60% of the students achieved the KKM score, totaling 18 students out of 30. Furthermore, in cycle 2, the implementation of the TPACK-based PjBL learning model showed significant improvement, with 27 students demonstrating enhanced learning outcomes, accounting for 90% who reached the KKM score. In conclusion, this study highlights the effectiveness of the TPACK-based project-based learning (PjBL) model in boosting student learning motivation in Class XI History at SMAN 1 Gunungsari.